Similarity-Based Interference and the Acquisition of Adjunct Control - Gerard, Juliana; Lidz, Jeffrey; Zuckerman, Shalom; Pinto, Manuela (Frontiers in Psychology, 2017)
Previous research on the acquisition of adjunct control has observed non-adultlike behavior for sentences like “John bumped Mary after tripping on the sidewalk.” While adults only allow a subject control interpretation for these sentences (that John tripped on the sidewalk), preschool-aged children have been reported to allow a much wider range of interpretations. A number of different tasks have been used with the aim of identifying a grammatical source of children’s errors. In this paper, we consider the role of extragrammatical factors. In two comprehension experiments, we demonstrate that error rates go up when the similarity increases between an antecedent and a linearly intervening noun phrase, first with similarity in gender, and next with similarity in number marking. This suggests that difficulties with adjunct control are to be explained (at least in part) by the sentence processing mechanisms that underlie similarity-based interference in adults.